FACTORS THAT INFLUENCE MENTAL HEALTH INFORMATION-SEEKING BEHAVIOR AMONG GENERATION Z - Gita Fitrisia; Hosizah Hosizah (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Generation Z, which is vulnerable to mental health problems, uses the internet as a primary source for obtaining information related to mental health. This study aims to determine the influence of demographic characteristics, digital literacy, and psychological conditions on mental health information-seeking behavior among Generation Z. This study used a quantitative approach with a cross-sectional design. Data collection was carried out by distributing online questionnaires consisting of a questionnaire on respondents' demographic characteristics, a digital literacy questionnaire adapted from the Indonesian Ministry of Communication and Information Technology (KOMINFO) questionnaire for measuring the 2022 Indonesian digital literacy index, DASS-42 to measure psychological conditions, and a questionnaire to measure mental health information-seeking behavior that has been tested for validity and reliability. Data analysis used descriptive analysis, classical assumption tests, and hypothesis testing using multiple linear regression tests. Gender and digital literacy variables partially influence mental health information-seeking behavior. Meanwhile, simultaneously, it was found that demographic characteristics, digital literacy, and psychological conditions significantly influence mental health information-seeking behavior among Generation Z by 42.1%, while the remaining 57.9% was influenced by other factors not examined in this study. The results of this study are expected to be a basis for madrasas in designing programs to improve digital literacy as well as awareness and handling of mental health problems among students.